Relato de um aluno no curso de medicina - Sicchieri, Felipe Defina (Universidade Federal de São Carlos, 2024)
This Course Completion Work (TCC) is foreseen in the Pedagogical Project of the UFSCar Medicine Course. This is a Critical-Reflective Narrative based on my experience reports as a student of this Undergraduate Course from 2018 to 2023, covering everything from entry into the course to passing through the 3 cycles that make up the course's curriculum.
Report from a student on the medicine course
Keywords: Graduação; Relato; Medicina; CIENCIAS DA SAUDE::MEDICINA